Comparative Effectiveness Analyses of Salvage Prostatectomy and Salvage Radiotherapy Outcomes Following Focal or Whole-Gland Ablative Therapy (High-Intensity Focused Ultrasound, Cryotherapy or Electroporation) for Localised Prostate Cancer. Issue 1 (January 2022) - Nathan, A.; Ng, A.; Mitra, A.; Sooriakumaran, P.; Davda, R.; Patel, S.; Fricker, M.; Kelly, J.; Shaw, G.; Rajan, P.; Sridhar, A.; Nathan, S.; et al.
Abstract: Aims: Ablative therapy, such as focal therapy, cryotherapy or electroporation, aims to treat clinically significant prostate cancer with reduced treatment-related toxicity. Up to a third of patients may require further local salvage treatment after ablative therapy failure. Limited descriptive, but no comparative, evidence exists between different salvage treatment outcomes. The aim of this study was to compare oncological and functional outcomes after salvage robot-assisted radical prostatectomy (SRARP) and salvage radiotherapy (SRT). Materials and methods: Data were collected prospectively and retrospectively on 100 consecutive SRARP cases and 100 consecutive SRT cases after ablative therapy failure in a high-volume tertiary centre. Results: High-risk patients were over-represented in the SRARP group (66.0%) compared with the SRT group (48.0%) ( P = 0.013). The median (interquartile range) follow-up after SRARP was 16.5 (10.0–30.0) months and 37.0 (18.5–64.0) months after SRT. SRT appeared to confer greater biochemical recurrence-free survival at 1, 2 and 3 years compared with SRARP in high-risk patients (year 3: 86.3% versus 66.0%), but biochemical recurrence-free survival was similar for intermediate-risk patients (year 3: 90.0% versus 75.6%). There was no statistical difference in pad-free continence at 12 and 24 months between SRARP (77.2 and 84.7%) and SRT (75.0 and 74.0%) ( P = 0.724, 0.114). Erectile function was more likely to be preserved in men who underwent SRT. After SRT, cumulative bowel and urinary Radiation Therapy Oncology Group toxicity grade I were 25.0 and 45.0%, grade II were 11.0 and 11.0% and grade III or IV complications were 4.0 and 5.0%, respectively. Conclusion: We report the first comparative analyses of salvage prostatectomy and radiotherapy following ablative therapy. Men with high-risk disease appear to have superior oncological outcomes after SRT; however, treatment allocation does not appear to influence oncological outcomes for men with intermediate-risk disease. Treatment allocation was associated with a different spectrum of toxicity profile. Our data may inform shared decision-making when considering salvage treatment following focal or whole-gland ablative therapy. Highlights: First comparison of salvage treatment for recurrent prostate cancer after ablative therapy. Salvage treatment oncological and functional outcomes are acceptable. Salvage radiotherapy may provide better oncological control. Salvage radiotherapy is associated with concomitant androgen deprivation therapy use and toxicity. Our data should be used to counsel patients before and after ablative therapy.